(untitled) (JOURNAL OF ADVANCES IN PHYSICS, 2015)
The molecular vibrations of Trichloro isocyanuric acid (C3Cl3N3O3) and Trithio cyanuric acid (C3H3N3S3) have been investigated in polycrystalline sample at room temperature by Fourier Transform Infrared (FT-IR) and FT-Raman spectroscopies in the region 4000-450 cm-1 and 4000-50 cm-1 respectively, which provide a wealth of structural information about the molecules. The spectra are interpreted with the aid of normal co-ordinate analysis following full structure optimization and force field calculations based on density functional theory (DFT) using standard B3LYP / 6-311++ G (d, p) basis set for investigating the structural and spectroscopic properties. The vibrational frequencies are calculated and the scaled values are compared with experimental FT-IR and FT-Raman spectra. The scaled theoretical wave numbers shows very good agreement with experimental ones. The complete vibrational assignments are performed on the basis of potential energy distribution (PED) of vibrational modes, calculated with scaled quantum (SQM) method. Stability of the molecule arising from hyper conjugative interactions, charge delocalization has been analyzed using natural bond orbital (NBO) analysis. The results show that change in electron density (ED) in Ïƒ* and anti-bonding orbitals and second order delocalizationenergy (E2) confirm the occurrence of Intra molecular Charge Transfer (ICT) within the molecule. The thermodynamic properties like heat capacity, entropy, enthalpy and zero point energy have been calculated for the molecule. The frontier molecular orbitals have been visualized and the HOMO-LUMO energy gap has been calculated. The Molecular Electrostatic Potential (MEP) analysis reveals the sites for electrophilic attack and nucleophilic reactions in the molecule.